Gambaran Tingkat Pengetahuan pada Remaja Tentang Seks Pranikah - Shifwatul Jayyidah Luthfi; Hendrik Probo Sasongko; Haswita Haswita (Akademi Kesehatan Rustida, 2021)
The teenage category is the most susceptible to any sexual behavior which treatents a health because of infected by any disease that be able to be transmitted through sexual contact. The bad behavior of sexual have any side effect namely contagious disease (HIV/AIDS, gonorrhea, syphilis and herpes genitalis), unwanted pregnancy and psichological trauma.The purpose of this study to know a level of knowledge in teenage about premarital sex at vocational high school XX Banyuwangi. The research design used a descriptive method. A variable from this research is a level of knowledge in teenage about premarital sex. The population from this research are students of grade 2 at vocational high school XX Banyuwangi totally for about 350 persons. A number of sampling were as many as 186 students by using quota technique. A data collection technique was using a questionnaire in the form a closed question. Most of respondents on the result of research in this level of knowledge who had sufficient level of knowledge as many as 95 persons (51,1%) a good level of knowledge as many as 64 persons ( 34,4%) and less level of knowledge as many as 27 persons ( 14,5%). Based on the result of research, it's important to increase health aducation about sexual education premarital sex in order to get prevent a side of premarital sex and they has been gotten true information which's meant to increase adolescent health service.